How to efficiently communicate between singers and listeners - Yu, Mengting (Kansas State University, 2022)
The purpose of this senior thesis is to explore how to communicate effectively as a singer with an audience or listeners. This paper explains the works chosen for the mezzo-soprano solo concert, understanding the repertoire as well as the composer's story and socio-historical content. The repertoire discussed in this paper includes Clara Schumann, Sechs Lieder Op, 13 a. Ich stand in dunklen träumen b. Sie liebten sich beide c. Liebeszauber d. Der Mond kommt still gegangen e. Ich hab'in deinem Auge F. Die stille lotosblume Barbara Strozzi's Udite amanti, L'Eraclito Amoroso Georges Bizet’s L'amour est un oiseau rebelle, from Carmen. This document was completed in partial fulfillment of the requirements for the Master of Music degree. The recital takes place on April 30, 2022, at 1:30 p.m., in All Faiths Chapel on the campus of Kansas State University.
Keywords: Carmen; Clara Schumann; Georges Bizet; Barbara Strozzi